History of Taenia saginata Tapeworms in Northern Russia - Konyaev, Sergey V. (Emerg Infect Dis, 2017)
Taenia saginata is the most common species of tapeworm infecting humans. Infection is acquired by eating cysticercus larvae in undercooked beef. A closely related species, T. asiatica, is found in eastern and southeastern Asia. The larvae of T. asiatica develop in viscera of pigs. In northern Russia, there is a third member of this morphologically indistinguishable group. Cysticerci of so-called northern T. saginata are found in cerebral meninges of reindeer, and the unique life cycle is dependent on a native custom of eating raw reindeer brain. We report the winding history of this mysterious tapeworm from the first reports to the present time. In addition, we confirm the position of this parasite as a strain of T. saginata by analyzing a mitochondrial DNA sequence of an archival specimen. The origin of this strain might date back to reindeer domestication and contacts between cattle-herding and reindeer-herding peoples in Asia.